The Ethnic Flower Festival of Ladakh, India: A Comprehensive Coverage of Sngo lha or Mendok rgyaspa - , Anwar Hussain; , Rinchan Dolkar; , Shabber Hussain; , Nazir Hussain (Archives of Current Research International, 2024)
The current study provides a comprehensive coverage of the Sngo lha or Mendok rgyaspa, the ethnic flower festival of Ladakh, India, a remote, high-altitude region known for its unique cultural traditions. In the face of modernization and religious restrictions, this time-tested festival has been abandoned or practiced on a limited scale, necessitating urgent efforts to revive it. Using a qualitative, ethnographic approach, the researchers conducted semi-structured interviews with 19 festival organizers and 42 prominent villagers, complemented by a review of 76 previously documented resources. The findings reveal how this annual celebration marks a transformative moment when Ladakh's barren landscapes blossom into a vibrant tapestry of colors, offering a unique glimpse into the region's rich traditions and the resilience of its residents. The study underscores the festival's multifaceted benefits, including its contributions to the sustainability of Ladakh's culture, environment, economy, and holistic development. Additionally, the research highlights how reviving this overlooked tradition could provide a significant boost to the region's tourism industry. As one of the few empirical studies documenting this festival, the current work lays the foundation for future research that can further explore the cultural, environmental, and socioeconomic dimensions of this endangered community practice.